2020
DOI: 10.1111/ppa.13150
|View full text |Cite
|
Sign up to set email alerts
|

Genomic sequencing indicates non‐random mating ofVenturia inaequalisin a mixed cultivar orchard

Abstract: Apple scab is one of the most economically important diseases of apples worldwide. The disease is caused by the haploid ascomycete Venturia inaequalis. Growing apples in cultivar mixtures may reduce disease severity. To determine how the pathogen population structure is affected by host mixtures we studied 24 V. inaequalis isolates sampled from three different apple cultivars (Bramley, Cox, and Worcester) growing in a mixed orchard approximately 50 years old. The isolates were aligned against a reference genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…So far, however, there have been no publications describing the cloning of Avr effector genes from V. inaequalis. Crucially, the genomes of multiple V. inaequalis isolates have been sequenced [18][19][20][21][22][23] and bioinformatic studies have identified a large catalogue of secreted, non-enzymatic proteinaceous effector candidates (ECs) from which candidate Avr effectors can be identified [19]. Most of these ECs belong to expanded (sequence-related) families [19]; however, the driving force behind the expansion of these families is not yet known.…”
Section: Introductionmentioning
confidence: 99%
“…So far, however, there have been no publications describing the cloning of Avr effector genes from V. inaequalis. Crucially, the genomes of multiple V. inaequalis isolates have been sequenced [18][19][20][21][22][23] and bioinformatic studies have identified a large catalogue of secreted, non-enzymatic proteinaceous effector candidates (ECs) from which candidate Avr effectors can be identified [19]. Most of these ECs belong to expanded (sequence-related) families [19]; however, the driving force behind the expansion of these families is not yet known.…”
Section: Introductionmentioning
confidence: 99%
“…Population differentiation was also observed in isolates collected from the same orchard from different apple host cultivars (Passey et al, 2020). Rvi6 (formerly known as Vf), from Malus floribunda clone 821, is the most frequently used apple scab resistance gene in apple breeding (Papp et al, 2020).…”
mentioning
confidence: 89%
“…Genome sequence reads of V. inaequalis isolates from BioProjects PRJNA407103 (Le Cam et al, 2019) and PRJNA354841 (Passey et al, 2020) were downloaded from NCBI using the SRA toolkit (https://trace.ncbi.nlm.nih.gov/Trace s/sra/sra.cgi?view=toolk it_doc). BioProjects PRJNA407103 (Le Cam et al, 2019) and PRJNA354841 (Passey et al, 2020) contain sequence reads of V. inaequalis (n = 103), V. asperata (n = 3), V. aucuparia (n = 1) and V. pirina (n = 3) representing 16 countries across North and South America, Europe and Asia.…”
Section: Publicly Available Genome Sequences Of V Inaequalismentioning
confidence: 99%
See 1 more Smart Citation
“…A key development over recent years has been the availability of several V. inaequalis genome sequences and gene catalogues (2, 59), as well as the development of both polyethylene glycol (PEG)-mediated protoplast and Agrobacterium tumefaciens -mediated transformation protocols for use with this fungus (10). However, while several V. inaequalis genes of interest that are putatively involved in the infection process of apple have been identified (5, 1115), none have been functionally characterized to date using traditional gene deletion or disruption techniques.…”
Section: Introductionmentioning
confidence: 99%